Actitudes del personal de salud de instituciones del Ministerio de Salud Pública sobre prevención, diagnóstico y tratamiento de tuberculosis pulmonar en la ciudad de Loja. - Cajamarca Viñán, César Elías (2015)
The present research is quantitative and descriptive in order to allow measure aspects of the information on the attitudes of people of MSP in some areas related to prevention, diagnosis and treatment of pulmonary tuberculosis in the city of Loja. The study was carried out in different health centers of the city of Loja as: “Centro de Salud No. 1, Chontacruz¸ Miraflores, Obrapia, Tierras Coloradas, Hugo González (CS No. 2), Daniel Alvarez, Heroes Cenepa, La Pradera, Zamora Huayco, Centro de Salud No. 3, Belén, Conzacola, Motupe, San Cayetano and Carigan”.In this research participated as universe all people who work in the centers health mentioned before, with the next sample: Doctores = 49, Nurses = 23 and Laboratory technicians = 3. Thus our sample of 67 persons.For the required technical information was used the Likert scale. This is a type of measurement instrument or data collection that is available in social research to measure attitudes, it consists of a set of items in the form of statements or trial by which the reaction (favorable or unfavorable, positive or negative) of individuals. That was applied to doctors, nurses and laboratory technicians, with the porpuse to identify the attitudes of health workers against pulmonary tuberculosis.The results show that there is an positive attitude of acceptance against the prevention, diagnosis and treatment of pulmonary tuberculosis according to recommendations made by the Tuberculosis control manual.